Financial Statement Analysis to Assess the Financial Performance of Palm Oil Companies Listed on the Indonesia Stock Exchange - Alfarizi, Muhammad; Sartika, Dewi (Sinergi International Journal of Management and Business, 2025)
This study examines the relationship between profitability, liquidity, solvency, and activity ratios and the financial performance of palm oil sub-sector firms listed on the Indonesia Stock Exchange. Based on a sample of 21 firms over the 2020–2021 period, multiple regression analysis was employed to test the hypotheses. The results show that profitability, liquidity, and solvency have significant positive effects on financial performance, while activity has a negative effect. These findings suggest that firms with strong profitability, liquidity, and solvency are more capable of signaling financial stability and attracting investor confidence. Conversely, higher activity ratios that do not correspond to efficiency may weaken performance. Overall, the evidence supports signaling theory by highlighting the role of financial ratios as key indicators that influence stakeholders’ perceptions of corporate performance.